Novel Techniques of Sperm Selection for Improving IVF and ICSI Outcomes - Oseguera-López, Iván; Ruiz-Díaz, Sara; Ramos-Ibeas, Priscila; Pérez-Cerezales, Serafín (Frontiers in Cell and Developmental Biology, 2019)
Almost 50% of the infertility cases are due to male factors. Assisted reproductive technologies (ARTs) allow to overcome the incapacity of these patients´ spermatozoa to fertilize the oocyte and produce a viable and healthy offspring, but the efficiency of the different techniques has still the potential to improve. According to the latest reports of the European Society of Human Reproduction and Embryology (ESHRE) and the Centers for Disease Control and Prevention of the USA (CDC), the percentages of deliveries per ART cycle in 2014 and 2016 were 21 and 22%, respectively. Among the reasons for this relatively low efficiency, the quality of the spermatozoa has been pointed out as critical, and the presence of high percentages of DNA-damaged spermatozoa in patients’ ejaculates is possibly one of the main factors reducing the ARTs outcomes. Thus, one of the main challenges in reproductive medicine is to ensure the highest quality of the spermatozoa used in ARTs, and specifically, in terms of genetic integrity. The latest techniques for the preparation and selection of human spermatozoa are herein discussed focusing on those proven to improve one or several of the following parameters: sperm genetic integrity, fertilization capacity, embryo production and in vitro survival, as well as pregnancy and delivery rates following in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI). In addition we discuss the potential of techniques developed in non-human mammals that could be further transferred to the clinic.